Dimensi Carter dalam Peningkatan Kualitas Layanan BPRS Bhakti Sumekar Sumenep - Ach. Zuhri; Rudy Haryanto (IQTISHADIA Jurnal Ekonomi & Perbankan Syariah, 2016)
Facing the public is increasingly critical as now, in addition to products, services provided also affect the sustainability of the company. Service as a form of first promotion to a prospective customer, if the superior service quality, the customer will continue to trade, and vice versa. To find out how much the service quality of a bank, it can use an analysis on a dimension that one of them is the Carter dimension (compliance, assurance, Reliability, tangibility, Emphaty, responsiveness) as a modified form of Servqual to fit used to measure the service quality Syariah banks. One of the Syari’a banks in Madura is Bank Pembiayaan Rakyat Syariah (BPRS) Bhakti Sumekar, that there is only one bank in Madura that there is a part of service quality, the task is to assess and evaluate all activities from the front liner (Security Guards, Tellers, Customer Service). This Research Methods use a qualitative approach, informants are the employees and customers of Bank Pembiayaan Rakyat Syariah (BPRS) Bhakti Sumekar. while techniques of data collection is by interview, observation, and documentation.  The results show that the first; all aspects of the Carter dimensions has been run and a good note, but the Tangibles dimension, there are some facilities are still inadequate, namely Parking Area and seating customers, parking area that less large makes the customers vehicle of the heat and rain resulted in anxiety of the customer will be safety, because it can damage their vehicles. Also customers seating is inadequate so that there are customers stand when waiting queues. The second; The strategy used BPRS Bhakti Sumekar namely innovation, that is not good to be good, and from the good to the better. By doing that, BPRS Bhakti Sumekar will always watch and evaluate each the service provided to customers. One of innovation proofs from BPRS Bhakti Sumekar is by to provide a suggestion box to accommodate the customer complaints, and free drinks such as tea and coffee so that customers do not feel tired and bored while waiting queues.